The Effect Of Capital Structure On Company Value With Roe As An Intervening Variable In The Banking Sector Listed In Bei 2015 – 2017 - Devy Dwi Puspitasari (NAROTAMA UNIVERSITY, Indonesia, 2019)
Company value is the investor's perception of the level of success of the company that is often associated with stock prices. This study aims to examine the effect of capital structure and ROE as an intervening variable on the corporate value of the banking sector listed on the Stock Exchange in 2015-2017.It used quantitative research with an approach that uses numerical data in statistical analysis. With a sample of 10 registered banks and provide financial reports to the Indonesia Stock Exchange (IDX) in the period 2015-2017. In this study using secondary data and with Partial Least Square (PLS) analysis techniques. Research shows that capital structure variables and ROE do not have a significant effect on firm value. While the capital structure has a positive and significant effect on ROE.